Serum-neutralizing antibody to VP4 and VP7 proteins in infants following vaccination with WC3 bovine rotavirus. - Ward, R L (1990)
Serum specimens from infants 2 to 12 months old vaccinated with the WC3 bovine rotavirus were analyzed to determine the relative concentrations of neutralizing antibody to the VP4 and VP7 proteins of the vaccine virus. To do this, reassortant rotaviruses that contained the WC3 genome segment for only one of these two neutralization proteins were made. The segment for the other neutralization protein in these reassortants was from heterotypic rotaviruses that were serotypically distinct from WC3. Sera were examined from 31 infants who had no evidence of a previous rotavirus infection and the highest postvaccination WC3-neutralizing antibody titers (i.e., 160 to 600) of the 103 subjects administered the vaccine. A reassortant (3/17) that contained both neutralization proteins from the heterotypic rotaviruses, i.e., EDIM (EW strain of mouse rotavirus) VP7 and rhesus rotavirus VP4, was not neutralized by these sera (geometric mean titer [GMT], less than 20). A reassortant (E19) that contained EDIM VP7 and WC3 VP4 was also very poorly neutralized by these antisera (GMT = 20). In contrast, antibody titers to a reassortant (R20) that contained WC3 VP7 and rhesus rotavirus VP4 were higher than those against WC3 (GMTs of 458 and 313, respectively). Thus, VP7 appeared to be the dominant immunogen for production of neutralizing antibody after intestinal infection of previously uninfected infants vaccinated with WC3 bovine rotavirus.